Ensino de lógica de programação para alunos do ensino fundamental utilizando a ferramenta scratch - SILVA, Leandro Orlando Sousa da (2019)
The present work aims to discuss the implementation of a programming logic teaching methodology for elementary school students, using the Scratch tool, motivated by the importance that programming can have for the development of a child. For this, starting from related works (DUARTE; SILVEIRA; BORGES, 2017; NASCIMENTO, 2015; RODRIGUES et al., 2016; SILVA; SOUZA; SILVA, 2016) and bibliographic review (OLIVEIRA et al., 2014; PAPERT, 1980; SOUZA; CASTRO, 2016; among others), a workshop with 11 meetings was conceived and offered to 12 students from the fifth year of a public elementary school located in the city of Belém, state of Pará. The first class was dedicated to teaching basic computer science, performing some activities and completing a form to identify the participant's profile. Lessons two through five were aimed at getting to know the Scratch tool and its block menus. Classes six to nine aimed at the development of some projects and, finally, classes ten and eleven, participants developed a project in Scratch autonomously and participated in a semi-structured interview. The observations made during the meetings, the analysis of the activities carried out, the profile of the participants and the interpretation of the "speeches" of the students were essences to obtain the results of the research. The main results are: (i) students' motivation to teach programming logic; (ii) the acceptability of the methodology and tool used; (iii) the development of logical reasoning; (iv) the stimulus to the development of computational thinking; and (v) the stimulation to enter the computer field and to learn in programming logic. It is inferred that the students of this workshop were able to acquire, in a short time, the initial concepts, however, basic for the programming, which demonstrates that it is possible and necessary to teach programming logic for children, and that its inclusion in the primary school curriculum.